Petrović-type inequality via fractional calculus - Péter Kórus; Juan Eduardo Nápoles Valdés; José Manuel Rodríguez; José Maríá Sigarreta Almira (Miskolc Mathematical Notes)
Inequalities play an important role in pure and applied mathematics. In particular, Petrović inequality is an important inequality which have several interesting generalizations. In this work we prove a new Petrović-type inequality for measurable functions defined on a space with finite measure, and we apply it to generalized Riemann–Liouville-type integral operators.